Two New Shellear Species (Gonorhynchiformes: Kneriidae), from the Luansa River (Upper Congo Basin): Hidden Diversity Revealed by Integrative Taxonomy - Lewis Ngoy Kalumba; Emmanuel Abwe; Frederic D. B. Schedel; Auguste Chocha Manda; Ulrich K. Schliewen; Emmanuel J. W. M. N. Vreven (Diversity, 2023)
Two new Kneria species, K. luansaensis sp. nov. and K. maxi sp. nov., are described from the Luansa River, a left bank tributary of the lower Luapula in the Bangweulu–Mweru ecoregion, based on an integrative approach using morphological and COI barcoding evidence. While K. luansaensis sp. nov. occurs from the source of the Luansa further downstream to above the last of the three Sanshifolo Falls, K. maxi sp. nov. only occurs downstream of all these three major falls. In Kneria, males of about ≥ 33 mm LS have an opercular and a postopercular organ. The number of lamellae on the latter seems to contain some alpha-taxonomic information, although this requires further study as allometric changes occur at about ≤ 45 mm LS. Additional external morphological characters differ between sexes, i.e., the (i) pectoral fin width (wider in males than females), (ii) dorsal fin height (longer in males than females), and (iii) length of the longest ray of the lower caudal fin lobe (longer in males than females). Agriculture, fishing with ichthyotoxines, and logging are the most pressing threats on the Luansa and thus to both the new species. Their discovery in one of the rivers of the Kundelungu Plateau and its surroundings located outside the present-day boundaries of the Kundelungu National Park highlights the need for a refined and improved protection strategy for this freshwater key biodiversity area.